2021
DOI: 10.21037/atm-21-3815
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the polarization states of the alveolar macrophages in chronic obstructive pulmonary disease samples based on miRNA-mRNA network signatures

Abstract: Background: Multiple gene expression studies have been performed to investigate the biomarkers of chronic obstructive pulmonary disease (COPD). However, few studies have related COPD to macrophage cells. Methods:The gene expression levels of clinical samples of COPD smokers (COPD; n=6), healthy smokers (Smoke; n=11), and never smokers (Never; n=4) were downloaded from the Gene Expression Omnibus (GEO) repository of GSE124180. The expression levels of messenger RNAs (mRNAs) and microRNAs (miRNAs) in macrophage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
(55 reference statements)
0
7
0
Order By: Relevance
“… 52 Besides, there was also a great difference in the composition of macrophages between COPD patients, smokers, and non-smokers; the proportion of M1 macrophages in smokers and COPD patients was lower than that of M0 and M2 macrophages. 53 The findings above further illustrated the importance of M0 macrophages to COPD. It should be noted that the differences in polarized macrophages between COPD patients and healthy controls were not statistically significant in this work.…”
Section: Discussionmentioning
confidence: 66%
“… 52 Besides, there was also a great difference in the composition of macrophages between COPD patients, smokers, and non-smokers; the proportion of M1 macrophages in smokers and COPD patients was lower than that of M0 and M2 macrophages. 53 The findings above further illustrated the importance of M0 macrophages to COPD. It should be noted that the differences in polarized macrophages between COPD patients and healthy controls were not statistically significant in this work.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, overexpression of circRNA_SLC8A1 inhibited the apoptosis, decreased Cleaved-caspase-3 protein expression in Mtb-infected macrophages, and promoted the survival of Mtb in macrophages, whereas overexpression of miR-20b-5p significantly reversed the effects of circRNA_SLC8A1 overexpression on Mtb-infected macrophages. Shen et al 31 reported that miR-20b-5p was higher expression in M2 macrophages, compared with M1 macrophages. Overexpressing miR-20b-5p suppressed the progression of chronic obstructive pulmonary disease by inhibiting macrophages to M1 phenotype by suppressing inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…For COVID-19-associated genes, we referred the PubChem ( https://pubchem.ncbi.nlm.nih.gov/#query=covid-19 ), CTD ( http://ctdbase.org/ ), DisGeNET ( https://www.disgenet.org/covid/diseases/summary/ ), baillielab net ( https://baillielab.net/maic/covid19 ) and KEGG DISEASE ( https://www.genome.jp/kegg/disease/ ) databases and data sets of ( Grant et al, 2021 ; Blanco-Melo et al, 2020 ; Mahmud et al, 2021 ; Singh et al, 2021 ; Overmyer et al, 2021 ; Mo et al, 2021 ). Regarding COPD-related genes, we considered DisGeNET ( https://www.disgenet.org/ ), CTD ( http://ctdbase.org/ ) and GeneCards ( https://www.genecards.org/ ) databases and data sets of ( O'Beirne et al, 2020 ; Han et al, 2021 ; Morrow et al, 2017 ; Hu et al, 2018 ; Raman et al, 2009 ; Huang et al, 2019 ; Morrow et al, 2019 ; Shen et al, 2021 ). These selected data sets above represent different clinical samples of COVID-19/COPD, specifically including alveolar lavage fluid, lung tissue, airway and peripheral blood.…”
Section: Methodsmentioning
confidence: 99%